2022
DOI: 10.1093/jac/dkac209
|View full text |Cite
|
Sign up to set email alerts
|

Ceftriaxone dosing based on the predicted probability of augmented renal clearance in critically ill patients with pneumonia

Abstract: Objectives PTA of protein-unbound ceftriaxone may be compromised in critically ill patients with community-acquired pneumonia (CAP) with augmented renal clearance (ARC). We aimed to determine an optimized ceftriaxone dosage regimen based on the probability of developing ARC on the next day (PARC,d+1; www.arcpredictor.com). Patients and methods Thirty-three patients enrolled in a prospective cohort study were admitted to the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…There are some directions for future research on dose optimisation of beta-lactam antibiotics in the critically ill. Dreesen and colleagues recently described a simulation that target attainment could be improved by doubling daily doses of ceftriaxone for patients with a prior increased risk of augmented renal clearance [32]. They showed that a machine learning approach could aid in dose optimisation.…”
Section: Discussionmentioning
confidence: 99%
“…There are some directions for future research on dose optimisation of beta-lactam antibiotics in the critically ill. Dreesen and colleagues recently described a simulation that target attainment could be improved by doubling daily doses of ceftriaxone for patients with a prior increased risk of augmented renal clearance [32]. They showed that a machine learning approach could aid in dose optimisation.…”
Section: Discussionmentioning
confidence: 99%
“…Drug excretion is increased in these patients, especially for hydrophilic antibiotics that are mainly excreted via the kidneys, such as beta-lactams. ARC has already been described as a risk factor of beta-lactam underdosing [14]. Without an initial dose adjustment to renal function, appropriate antibiotic therapy is delayed.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, presumed or established ARC, defined as either estimated CL CR (using the Cockcroft–Gault formula) > 130 mL/min or glomerular filtration rate (estimated using the CKD-EPI equation) > 96.5 mL/min/1.73 m 2 , 54 although associated with suboptimal drug exposure, was reported in only five studies, 32 , 55–58 and investigated as a covariate in two. 57 , 59 One of these studies, looking at critically ill patients with pneumonia and preserved renal function, found the inclusion of ARC to improve model fit. This remains an under-investigated covariate.…”
Section: Discussionmentioning
confidence: 99%